Chartered cabs - Roy, Debjit, (SAGE Knowledge. Cases., 2017)
The market share of Chartered Cabs is affected by new entrants in Ahmedabad. In addition, their operational costs are soaring due to excessive dry run costs. Due to immense competition, Chartered needs to focus on high service quality delivery and also minimize its operational costs. This case will allow the participants to understand the operational complexities of a cab service provider and also arrive at alternate strategies to minimize costs.